Word Find Games for Learning Vocabulary in Junior High School - Robi'atul Addawiyyah; Yayu Heryatun; Rohman Rohman (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2023)
This research discussed learning vocabulary in 8th grade junior high school through mobile games (Word Find). To get the results, researchers used the pre-experimental research design which was carried out to 8th junior high school at MTsN 5 Tangerang. The population used is 35 students in one class. The researchers used purposive sampling. Researchers used tests in the research. There are two tests, namely pre-test and post-test. Pre-test and post-test were conducted to compare whether the implementation of mobile games was effective or not in this research. The data were collected using pre-test and post-test. The result showed that the average pre-test result is 5.22 and the average post-test result is 8.1. According to the data, the value of is bigger than, = 0,046 > = -2,032. So, Ho is rejected and Ha is accepted. It means this application is effective and the teachers can use a Word Find application as vocabulary learning media.